Impact of Physical Activity on Quality of Life After Coronary Artery Bypass Surgery - Vilma Dudonienė; Aleksandras Kriščiūnas; Akvilė Matukonytė (Lithuanian Sports University, 2020)
Physical therapy and regular physical activities (housekeeping, working outside, going up the stairs, walking or riding a bicycle), have many benefits for physical state in patients with heart diseases. Better physical state ensures patients' well-being  and independence. The goal of cardiac rehabilitation program is not only to prolong life but also to improve physical functioning, symptoms, well-being, and health-related quality of life [1]. The aim of this study was to evaluate changes in the quality of life and determine the indices of 6 min walk after applying four-week physiotherapy, and one-year home activity program in patients who had undergone coronary artery bypass surgery. The tasks were to evaluate quality of life and determine the indices of 6 min walk in patients after coronary artery bypass surgery: 1) before physiotherapy; 2) after four-week physiotherapy in rehabilitation centre; and 3) after 12 months after surgery. The participants were 20 male patients (their mean age was 59.9 ± 4.83 years) who had undergone coronary artery bypass surgery. The patients completed 40 physiotherapy classes of 40-45 minutes (4 weeks, two times a day five days a week) in Virsuziglis Rehabilitation Centre. Besides, a home activity program for 12 months was prescribed for all patients to promote and maintain their physical activity. Measures: quality of life according to EQ-5D and the indices of 6 min walk were measured. Results: the indices of 6 min walk significantly increased after 4 weeks of physiotherapy and 12 months post surgery. After 4 weeks of physiotherapy the patients reported significant improvements in three of five dimensions of the quality of life. Significant improvements in the quality of life were defined 12 months post surgery. Conclusions: the quality of life and indices of 6 min walk test 12 months after coronary artery bypass surgery improved significantly. Keywords: coronary artery bypass, physical therapy, quality of life, 6 min walk test.